The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5194/angeo-33-1203-2015
|View full text |Cite
|
Sign up to set email alerts
|

The far-ultraviolet main auroral emission at Jupiter – Part 1: Dawn–dusk brightness asymmetries

Abstract: Abstract. The main auroral emission at Jupiter generally appears as a quasi-closed curtain centered around the magnetic pole. This auroral feature, which accounts for approximately half of the total power emitted by the aurorae in the ultraviolet range, is related to corotation enforcement currents in the middle magnetosphere. Early models for these currents assumed axisymmetry, but significant local time variability is obvious on any image of the Jovian aurorae. Here we use far-UV images from the Hubble Space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 29 publications
2
30
2
Order By: Relevance
“…In our simulations, the main oval is also slightly brighter at dusk than at dawn. This dusk‐dawn asymmetry of the brightness of the main oval has been observed by Bonfond et al [].…”
Section: How Does the Solar Wind Density Influence The Ionospheric Cusupporting
confidence: 77%
“…In our simulations, the main oval is also slightly brighter at dusk than at dawn. This dusk‐dawn asymmetry of the brightness of the main oval has been observed by Bonfond et al [].…”
Section: How Does the Solar Wind Density Influence The Ionospheric Cusupporting
confidence: 77%
“…These have been shown to occur near-constantly and manifest as spikes in the dusk power (Figure 1e), but they do not fully account for the underlying steady asymmetry between dawn and dusk which we observe here. At Jupiter, a similar asymmetry was observed and suggested to be related to a partial ring current in the nightside magnetosphere (Bonfond et al, 2015), but it is unclear whether a similar process could be important in Saturn's magnetosphere. The case study presented in Figure 1 is not the only quiet sequence observed.…”
Section: Saturn's Quiet Main Aurora: Subcorotational and Ppo Systemscontrasting
confidence: 75%
“…Since Jupiter's magnetic axis is tilted by only ~10° with respect to the spin axis, Earth‐orbiting observatories can only capture one portion of Jupiter's aurora at the time. Therefore, we follow the methodology described by Bonfond et al () in which the closure of the contour is achieved with a Fourier series. This effect was also accounted for in Figure and Table , where the emitted power is corrected for the viewing geometry by a time‐dependent factor equal to the ratio between the total area of the subregion of interest and the area of its portion visible from Earth (Nichols, Clarke, Gérard, Grodent, & Hansen, ).…”
Section: Auroral Power and Subregionsmentioning
confidence: 99%